Untangling the seasonal dynamics of plant-pollinator communities - Bernat Bramon Mora (Nature Portfolio, 2020)
Plant-pollinator interactions are not fixed but instead can change seasonally and across years. Here, the authors provide a holistic perspective on how plants and pollinators first enter, then comprise, and ultimately leave interaction networks over time.